The Rights of the Dying Child and the Duties of Healthcare Providers: The "Trieste Charter". Issue 1 (January 2017) - Benini, Franca; Vecchi, Roberta; Lazzarin, Pierina; Jankovic, Momcilo; Orsi, Luciano; Manfredini, Luca; Drigo, Paola; Sellaroli, Valentina; Gangemi, Michele; Spizzichino, Marco; Orzalesi, Marcello
Purpose: The death of a child is a devastating and tragic event for all those involved. This charter aims to help healthcare workers and people assisting terminally ill children to recognize some important rights of the child, with some related suggestions. We consider it important to have a trace of this process, based on the skillfulness of long-lasting experts. Methods: In September 2012, a group of professionals working with children affected by incurable illness in Italy launched a project to formulate the charter. Trieste is the city where the group of professionals first met to start the project. The first step was a detailed literature search on the topic, the second step was an extensive discussion among the professionals (writing committee) to prepare a first draft; later (third step) the draft was revised by 38 experts in different areas, including patient and family representatives, and lastly (fourth step) the final version of the charter was prepared. Results: We developed a document containing 10 rights and corresponding duties that could be applied to any clinical situation or circumstances and used as a guide by professionals and families caring for children in the terminal stages of an illness. Conclusions: The Trieste Charter proposes fundamental rights for children who are approaching the end of their lives. The charter will have achieved its purpose when every person caring for a dying child is capable of staying near the child until the last moments of his or her life, prepared to accept his or her death, ensuring both respect and dignity.